Analisis Pengaruh Kebijakan Hutang Terhadap Kinerja Keuangan Perusahaan - Andi Kurniawati (Akademi Akuntasi Effendiharahap, 2023)
This study aims to analyze the influence of Net interest margin (NIM), Deposits (DEP), Loans (LOA), and Size Bank (SIZE) to Capital Adequacy Ratio (CAR) variables. Hypothesis testing in this study using multiple regression analysis (Multiple Regression). The sample used in this study were 28 banking companies listed in the Indonesia Stock Exchange (IDX) with a purposive sampling techniques, namely engineering samples based on the determining criteria. Those criteria are banking companies listed on the Stock Exchange in 2012 - 2015 and submit annual financial statements and complete. After partial hypothesis test showed that NIM has positive and significant effect to CAR, negative DEP is not significant to CAR, LOA is significant to CAR, and SIZE has negative and insignificant effect on CAR.